Swedish Drama Dialogue - Mats Thelander; Görel Bergman-Claeson; Ulla Börestam; Ulla Melander Marttala; Kristina Ohlander; Siv Strömquist; Marie Sörlin; Kerstin Thelander; Carin Östman; Gun Widmark; Linnéa Anglemark; Merja Kytö; et al. (University of Gothenburg, 2026)
Swedish Drama Dialogue is a corpus of Swedish drama dialogue from the period 1730–1950, consisting of 34 complete
plays.
In 1998, teachers and researchers at the Department of Scandinavian Languages at Uppsala University initiated the
project Svensk dramadialog över tre sekler (’Swedish Drama Dialogue over Three Centuries’). The project was
funded by the Faculty of Languages at Uppsala University and the former Swedish Council for Research in the
Humanities and Social Sciences (HSFR). The principal investigator was Mats Thelander; other participants from the
outset included Görel Bergman Claeson, Ulla Börestam, Ulla Melander Marttala, Siv Strömquist, Gun Widmark, and
Carin Östman. The digitisation and encoding of the dramas were carried out by Kristina Ohlander at the department
of Linguistics and Philology, Uppsala University. The project is presented in research reports Svensk
dramadialog (’Swedish Drama Dialogue’) no. 1 (Melander Marttala & Östman 2000) and no. 2 (Melander Marttala &
Strömquist 2001). A substantial number of focused studies based on the project have since been conducted and
published in later reports, articles, and anthologies by both project members and other researchers within and
beyond Uppsala.
The material originally consisted of 45 complete Swedish plays dating from 1730 to the late 1990s, divided into
dialogue and metatext. The plays were selected with diachronic comparability in mind and, as far as possible,
comprised original Swedish plays for adult audiences that had been performed and whose authorship could be clearly
identified. The selection aimed to reflect natural language use for each period; consequently, contemporary plays
were prioritised and verse drama was largely avoided.
At a later stage (after 2009), a subset of the material was annotated and processed for reuse in the corpus
English and Swedish Drama Dialogue 1725–1950 (ESDD). This corpus comprised 15 English and 15 Swedish plays and
was a collaborative project between the Department of Scandinavian Languages and the Department of English at
Uppsala University. Work on ESDD was carried out by Linnéa Anglemark, Merja Kytö, Ulla Melander Marttala, and
Sofia Gustafson Capcová, with support from the Faculty of Languages at Uppsala University.
The remaining plays have been processed by Astrid Berntsson Ingelstam with support from Språkbanken CLARIN, funded
by the Swedish Research Council (2025–2028; grant no. 2023-00161) in collaboration with the ten participating
universities and government agencies.

Lärare och forskare vid Institutionen för nordiska språk i Uppsala inledde 1998 projektet Svensk dramadialog
under tre sekler. Finansiärer var Språkvetenskapliga fakulteten vid Uppsala universitet och dåvarande HSFR.
Huvudansvarig för projektet var Mats Thelander; medverkade från början gjorde också Görel Bergman Claeson, Ulla
Börestam, Ulla Melander Marttala, Siv Strömquist, Gun Widmark och Carin Östman. För digitalisering och kodning av
dramatexterna anlitades Kristina Ohlander vid Lingfil. Projektet presenteras i forskningsrapporterna Svensk
dramadialog nr 1 (Melander Marttala & Östman 2000) och nr 2 (Melander Marttala & Strömquist 2001). Ett betydande
antal punktstudier från projektet har genomförts och publicerats i senare rapporter, artiklar och antologier av
såväl projektdeltagarna själva, som av andra forskare i och utanför Uppsala.
Materialet bestod av 45 oavkortade svenska skådespel från 1730 till sent 1990-tal uppdelade på dialog och
metatext. Dramerna hade valts ut med diakronisk jämförbarhet i åtanke och var så långt möjligt svenska
originaldramer för vuxna som blivit uppförda och har en identifierbar författare. Urvalet syftade till att spegla
naturligt språk från respektive tidsperiod, varför man i första hand valt samtidsdramer och undvikit dramer
skrivna på vers.
I ett senare skede (efter 2009) har en delmängd av materialet annoterats och bearbetats för återanvändning i
korpusen Engelsk och svensk dramadialog 1725–1950 (ESDD). Korpusen innehöll 15 engelska och 15 svenska dramer,
och var ett samarbetsprojekt mellan Institutionen för nordiska språk och Engelska institutionen vid Uppsala
universitet. Arbetet med ESDD genomfördes av Linnéa Anglemark, Merja Kytö, Ulla Melander Marttala och Sofia
Gustafson Capcová, med stöd från Språkvetenskapliga fakulteten vid Uppsala universitet.
Resterande dramer har bearbetats av Astrid Berntsson Ingelstam med stöd av Språkbanken CLARIN, finansierat av
Vetenskapsrådet (2025–2028; grant 2023-00161) tillsammans med de 10 medverkande universiteten och myndigheterna.
Svensk Dramadialog
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik